2020
DOI: 10.3389/fphar.2019.01625
|View full text |Cite
|
Sign up to set email alerts
|

UPLC-Q-TOF-MS Study of the Mechanism of THSWD for Breast Cancer Treatment

Abstract: Taohong Siwu decoction (THSWD) is a classic traditional Chinese medicine (TCM) prescription that is widely used in the clinical treatment of gynecological and cerebrovascular diseases. Here we used a method that coupled ultra-performance liquid chromatography to quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS) in which both positive and negative ion modes were established to investigate the major constituents in THSWD. A Waters ACQUITY UPLC BEH C18 column (2.1 mm×100 mm, 1.7 mm) was used to separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…Therefore, it is important to evaluate the pharmacokinetics of THSWD in vivo. We previously studied the efficacy of THSWD, and showed that THSWD promoted blood circulation, protected against cerebral ischemia, and relieved pain [11,12], and we confirmed that THSWD has a definite therapeutic effect on breast cancer, and studied its mechanism of action [13]. However, few studies have identified active substances absorbed from THSWD.…”
supporting
confidence: 57%
“…Therefore, it is important to evaluate the pharmacokinetics of THSWD in vivo. We previously studied the efficacy of THSWD, and showed that THSWD promoted blood circulation, protected against cerebral ischemia, and relieved pain [11,12], and we confirmed that THSWD has a definite therapeutic effect on breast cancer, and studied its mechanism of action [13]. However, few studies have identified active substances absorbed from THSWD.…”
supporting
confidence: 57%
“…Their respective contents of hydroxysafflor yellow A, amygdalin, paeoniflorin, ferulic acid, verbascoside, and ligustilide in THSWD were identified as 0.198, 0.45, 0.602, 0.031, 0.014, and 0.256 mg ml −1 (Chen et al, 2020). Also, our previous report has investigated the major constituents of THSWD by UPLC-Q-TOF-MS. A total of 95 components have been identified, including aromatic acids, flavonoids, polysaccharides, volatile oils, monoterpene glycosides, aromatic cyanoglycosides (Duan et al, 2019). Many published articles have confirmed that they are the basis of THSWD inhibitors of pyroptosis (Liu et al, 2017;Ye et al, 2020;Yin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…According to the degree of node correlation, the order was as follows: Isatdis Radix (4th, yang tonic) [52], Forsythia Fructus (11th, Antipyretic and antidote) [53], Ginkgo Folium (5th, Antitussive and antiasthmatic drugs) [54], Mori Cortex (3rd, Antitussive and antiasthmatic drugs) [55], Licorice (1st, reinforcing drugs) [56] and Radix Salviae (2nd, Drugs with the e cacy of modifying rheological properties of blood) [57]. Aqueous extract of Chinese medicinal compound is the most common method to study compound components [58,59]. Hence, we sought points that were uniformly scattered on the domain [60,61], furthermore, we did a multi-nonlinear regression analysis to search for the optimal combination in preliminary experiments.…”
Section: Discussionmentioning
confidence: 99%